Practical Informatics for Cytopathology - Pantanowitz, Liron; Parwani, Anil V.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Practical Informatics for Cytopathology provides a concise and practical overview of pathology informatics. The book offers a succinct overview of basic computing and laboratory information systems applied specifically to the field of cytopathology. Readers are exposed to emerging areas in pathology informatics, such as specimen tracking and digital imaging. Valuable features of this volume include summary tables, diagrams, vital resources and a glossary of informatics terms to help readers. Written by authorizes in the field, Practical Informatics for Cytopathology is a vital resource that provides users with a solid, comprehensive foundation and practical working knowledge of the rapidly emerging field of pathology informatics.
Introduction to Informatics -- Basic Computing -- Networking -- Databases -- Coding -- Laboratory Information Systems -- Laboratory Information System Operations and Regulations -- Reporting -- Quality Management -- Barcoding -- Informatics Projects -- Lean Six Sigma -- Electronic Medical Records -- Digital Imaging -- Automated Pap Tests -- Telecytology -- Cytology Online -- Bioinformatics -- Research Informatics.
Keywords: Medicine; Medical laboratories; Pathology; Medicine & Public Health; Pathology; Laboratory Medicine